Revision of the subgenus Mesopraocis Flores & Pizarro-Araya of the Neotropical genus Praocis Eschscholtz (Coleoptera: Tenebrionidae: Pimeliinae) - Flores, Gustavo Ernesto (2022)
The second part of a revision of the species of the genus Praocis Eschscholtz is presented. The subgenus Mesopraocis Flores & Pizarro-Araya, distributed in northern Chile from 25° South to 31° South, is revised. This article includes a redescription of the subgenus, redescriptions of its species, an identification key, and a discussion on morphological adaptations of the species to fossorial life. Habitus photographs, scanning electron micrographs of head, antennae, prosternum, abdomen, and protibiae, illustrations of genital features, and distribution maps are presented. Conical pegs sensilla on tibiae are described and illustrated using SEM for the first time for a South American tenebrionid species. A new Praocis species is described: Praocis (Mesopraocis) arenicola sp. nov. Praocis (Mesopraocis) flava Kulzer, 1958 is synonymised with P. (M.) pilula Laporte, 1840. Other species of the subgenus are: P. (M.) calderana Kulzer and P. (M.) nitens Kulzer. A statement on the variation in the number of antennomeres in P. (M.) pilula is appended.